Design Faster, Code Smarter: Web Design With SASS - Hidayat, Taufik; Anjani, Meisya Putri; Afkarinah, Afni Izzah; Aullia, Mochammad Rizqi; Mujiastuti, Rully; Nurbaya Ambo, Sitti; Sutrisno, Mirza; Rosanti, Nurvelly (Edumedia Solution, 2025)
The